English English - Bagas Arisa Atmaja Putra; Sukirman Sukirman (Jurnal Teknologi Informasi dan Pendidikan, 2023)
The large number of students who like to play games and conventional learning media causes students' lack of interest in learning, and an interesting learning media is needed for students. This research was conducted to develop and determine the feasibility of learning media based on multiplayer educational games. This study used the ADDIE development model. The trial process was carried out with media tests, material tests, and direct implementation on 29 grade VII students of SMP Negeri 4 Ngawi. The results of this study show the feasibility rate carried out by media experts of 83% with a very decent category, the feasibility tested by material experts was 93% with a very proper class, and the results of the satisfaction questionnaire were filled out by students. calculated using SUS calculations showing a value of 80.6 with the EXCELLENT category including grade scale B, it can be concluded from these results that this multiplayer educational game-based learning media is suitable for use as a learning medium.